O LÚDICO COMO INTERMEDIADOR DAS AULAS DE EDUCAÇÃO FÍSICA: A IMPORTÂNCIA DOS BRINQUEDOS E BRINCADEIRAS - de Souza, Edima Ferreira; Ferreira Freitas, Ronilson (RENEF, 2022)
ABSTRACT Playful activities are important, as they help in the harmonious evolution of the individual, especially in early childhood, as games and toys involve social interaction, in addition to developing affectivity and mental health. Playfulness contributes to the individual’s overall development, facilitating the process of expression and construction of thought. In this context, this study aimed to describe play as an intermediary process of learning in Physical Education classes, with emphasis on toys and games. To achieve the proposed objectives, a research with bibliographic procedures, exploratory of a qualitative nature, was carried out. It is concluded that teaching in early childhood education in Physical Education classes should be associated with playing, because in play, the professional can pedagogically intervene in care and education actions between the child and knowledge, as the main indicator of learning among children it is the role they play while they play. Key Words: Child education. Physical education. Playfulness. Cognitive Development. Motor development.